The Study of Biodive and Cow Fertilizer Composition on Bean Growth and Production (Phaseolus Vulgaris L.) - Santosa, Sartono Joko; Maulida, Elly Istiana; Nuraini, Sinta (jfpublisher, 2022)
In agricultural cultivation technology, there are very influential limiting factors on plant growth and yield, one of which is the presence of fertilization. This research aims to study the composition of Bio fertilizer and Cow manure fertilizer application bean’s growth and yield. This research was conducted from February 25th, 2022 to May 22th, 2022 at Seed Garden of Food Crops and Horticulture Tawangmangu (TPH) Tawangmangu, Karangpandan District, Karanganyar Regency with an altitude place of 1100 meters above sea level and Latosol soil. This research method uses a single factor randomized complete block design (RCBD) consisting of 6 kinds of experiments and each was repeated 4 times in order to obtain 24 kinds trial. The variables used are length of plant, number of leaves, length of root, fresh weight of biomass, dry weight of biomass, the number and weight of pods. The results of this research showed that the composition of biofertilizer and cow fertilizer application has no effect on bean’s growth and yield.